2016
DOI: 10.1021/acs.jctc.5b01169
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Kinetic Isotope Effects from First-Principles Path Sampling Calculations

Abstract: In this study, we develop and test a method to determine the rate of particle transfer and kinetic isotope effects in enzymatic reactions, specifically yeast alcohol dehydrogenase (YADH), from first-principles. Transition path sampling (TPS) and normal mode centroid dynamics (CMD) are used to simulate these enzymatic reactions without knowledge of their reaction coordinates and with the inclusion of quantum effects, such as zero-point energy and tunneling, on the transferring particle. Though previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In recent work, we developed a method to calculate KIEs from first principle path sampling calculations (Varga & Schwartz, 2016). As in the above described study, TPS and CMD were utilized to circumvent limitations of other techniques dealing with the transfer of quantum particles.…”
Section: New Methods For Calculation Of Values Relevant To Enzyme Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent work, we developed a method to calculate KIEs from first principle path sampling calculations (Varga & Schwartz, 2016). As in the above described study, TPS and CMD were utilized to circumvent limitations of other techniques dealing with the transfer of quantum particles.…”
Section: New Methods For Calculation Of Values Relevant To Enzyme Mmentioning
confidence: 99%
“…In recent work, the rate algorithm with CMD was applied to the calculation of the primary H/D KIE in yeast alcohol dehydrogenase (Varga & Schwartz, 2016). This is the first application of the Chandler rate algorithm to an enzyme, as well as the first application in tandem with CMD.…”
Section: New Methods For Calculation Of Values Relevant To Enzyme Mmentioning
confidence: 99%
“…[51,52] Trajectorybased dynamics has also been applied to investigate H/D isotope effect on an ESPT. [53] However, the application of such a method to the present solution system is computationally too demanding because of the conformational flexibility of heptane and the need to model the solute by DFT.…”
Section: Differences In Gspt Reaction In An Isolated Cluster and Inmentioning
confidence: 99%
“…They identified a conserved evolutionary motif in horse liver ADH that spans the catalytic and coenzyme binding domains (including Ser‐144, Gly‐181, Val‐203, Gly‐204, Val‐207, Glu‐267, Ile‐269, and Val‐292) and could participate in catalysis. They used transition path sampling to conclude that “protein compression” in the homologous yeast ADH “mediates a near barrier‐less hydride transfer.” They suggested that “slight changes in promoting vibrations (in lactate dehydrogenase) result in dramatic changes in enzyme chemistry.” The contribution of such fast dynamics to catalysis of hydride transfer by ADH needs experimental evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…They used transition path sampling to conclude that "protein compression" in the homologous yeast ADH 51 "mediates a near barrier-less hydride transfer." 52,53 They suggested that "slight changes in promoting vibrations (in lactate dehydrogenase) result in dramatic changes in enzyme chemistry." 54,55 The contribution of such fast dynamics to catalysis of hydride transfer by ADH needs experimental evaluation.…”
Section: Introductionmentioning
confidence: 99%